Chronic respiratory symptoms and associated factors among cement factory workers in Dejen town, Amhara regional state, Ethiopia, 2015 - Gizaw, Zemichael (Multidiscip Respir Med, 2016)
BACKGROUND: Chronic respiratory diseases represent a public health challenge in both industrialized and developing countries. Chronic respiratory symptoms are more prevalent in cement factories of developing countries, where occupational health and safety issues are less emphasized. This study was conducted to determine the prevalence and factors affecting chronic respiratory symptoms among workers in Dejen cement factory, 2015. METHODS: Institution based cross sectional study was conducted among 404 randomly selected study participants. Data were collected through interviewer administered structured questions derived from British Medical Research Council (BMRC) adult respiratory symptom assessment questions and observational check lists for the assessment of dust exposure, hygienic practices and use of personal protective equipments. Multivariable logistic regression model was used to identify predictor variables which have association with chronic respiratory symptoms and finally the variables which had significant association were identified on the basis of Adjusted Odds Ratio (AOR) with 95 % Confidence Interval (CI) and p < 0.05 RESULTS: The prevalence of chronic respiratory symptoms among Dejen cement factory workers was 62.9 %, with prevalence of chronic cough 24.5 %, chronic wheezing 36.9 %, chronic phlegm 24.5 %, chronic shortness of breath 38.6 %, and chest pain 21.0 %. Chronic respiratory symptoms were associated with sex (AOR = 2.07, 95 % CI = 1.18, 3.63), age (AOR = 4.20, 95 % CI = 1.94, 9.12), education level (AOR = 4.07,95 % CI = 1.86, 8.92), cement mill (AOR = 3.72, 95 % CI = 1.92, 7.21), burner and clinker (AOR = 2.28, 95 % CI = 1.18, 4.43), work experience (AOR = 5.44, 95 % CI = 3.09, 9.59), training on occupational safety and health (AOR = 2.73, 95 % CI = 1.41, 5.29), smoking (AOR = 5.38, 95 % CI = 1.42, 20.39) and chronic respiratory diseases (AOR = 7.79, 95 % CI = 2.02, 30.04). CONCLUSION: Chronic respiratory symptoms were highly prevalent among Dejen cement factory workers. Age, sex, education level, working department, smoking, work experience, and training were identified factors. Pre employment and on service training, smoking cessation programs, improving hygienic practices are important tasks in order to maintain the health and safety of workers.